Economic Impacts of Logging Intensities in the Muda-Pedu Forested Catchment, Kedah, Malaysia - Yacob, Mohd Rusli (2002)
This study was conducted primarily to determine benefits associated with logging and to quantify the cost associated with sedimentation in the Muda and Pedu Forested Catchments, Kedah. Data on timber value were obtained form the Ulu Muda experimental site and those on the rate of sediment yield were obtained from a study by Lai et al. (1999). The estimated NPV of timber under conventional logging (CL) and modified logging (ML) were RM 119.4 million and RM87.9 million respectively for a land area of 118,673 ha over a two cutting cycles of 30 years each. The average sediment yield in the Muda and Pedu Catchments was estimated to be 77.9 tonne/ha/year under catchment protection (CP), 188 tonne/ha/year under conventional logging (CL) and 115.5 tonne/ha/year under modified logging (ML). Meanwhile, the estimated NPV of treated water production under catchment protection (CP) was RM 128.8 million, under conventional logging (CL) was RM 121.3 million and under modified logging (ML) was RM 125.8 million. The incremental NPV (ML-CP) under modified logging option (ML) was very small valued at RM3.0 million as compared with the conventional logging (CL) with RM7.5 million. The small average incremental NPV under modified logging (ML) was due to the low incremental NPV gained when compared to the conventional logging option. The rise in the sediment concentration caused by CL option was not high enough to cause a high increase in water treatment plant. The above analysis supported conventional logging option over modified logging when only the off-site cost of sedimentation is incorporated This analysis is inconclusive since other physical impacts of logging have not been incorporated such as the potential welfare loss of biodiversity and climate benefits of protected forest. Nevertheless, the analysis has shown that logging does provide off-site cost in the form of higher water treatment costs. This kind information could be useful to policy makers when deciding upon land use options.